Correlation Between Cystatin C and the Severity of Cardiac Dysfunction in Patients with Systolic Heart Failure - Ge J; Ji Y; Wang F; Zhou X; Wei J; Qi C (Dove Medical Press, 2023)
Jiyong Ge,1 Yuan Ji,1 Fangfang Wang,1 Xuejun Zhou,1 Jiazhan Wei,1 Chunjian Qi2 1Department of Cardiology, The Affiliated Changzhou Second People's Hospital of Nanjing Medical University, Changzhou, Jiangsu, 213003, People's Republic of China; 2Oncology Institute, The Affiliated Changzhou Second People's Hospital of Nanjing Medical University, Changzhou, Jiangsu, 213003, People's Republic of ChinaCorrespondence: Chunjian Qi, Oncology Institute, The Affiliated Changzhou Second People's Hospital, Nanjing Medical University, Xinglong Alley 29, Changzhou, Jiangsu, 213003, People's Republic of China, Tel +86 519 88119730, Fax +86 519 88115560, Email qichunjianedu@outlook.comIntroduction: To investigate the relationship between cystatin C and cardiac dysfunction severity in patients with systolic heart failure.Methods: We recruited 100 hospitalized patients with systolic heart failure and 100 age-gender-matched controls. The clinical information of each patient was collected. Blood pressure, heart rate, height, and weight were measured, as were serum concentrations of cholesterol, renal function indices, cystatin C, and B-type natriuretic peptide (BNP). Transthoracic echocardiography was performed on each patient.Results: Cystatin C and other indices of renal function, such as urea nitrogen, creatinine, and uric acid, were significantly elevated in the serum of patients with heart failure and those with more severe cardiac dysfunction. The stepwise regression analyses showed that cystatin C was positively associated with BNP (β = 0.18, P = 0.04, 95% CI: 21.1 ~ 1420.4) and left atrial diameter (LAD) (β = 0.19, P = 0.04, 95% CI: 0.03 ~ 9.21) and was negatively associated with ejection fraction (β = − 0.22, P = 0.023, 95% CI: − 12.4 ~ − 0.93), while creatinine was only positively correlated with BNP (β = 0.23, P = 0.03, 95% CI: 1.11 ~ 20.7). The Receiver Operating Characteristic (ROC) curves demonstrated significantly more severe cardiac dysfunction (NYHA III/IV) in patients with cystatin C ≥ 0.895mg/L (sensitivity was 83.0%, specificity was 80.9%, AUC = 0.893) and creatinine ≥ 91.5μmol/L (sensitivity was 71.7%, specificity was 70.2%, AUC = 0.764).Conclusion: Cystatin C was significantly correlated with cardiac structure and function in patients with systolic heart failure, and it was more valuable than creatinine to evaluate the severity of heart failure.Keywords: cystatin C, renal function, systolic heart failure